Diet and risk for hernia: a Mendelian randomization analysis - Yang, Yanjiang; Han, Biao; Yang, Wenwen (Frontiers in Nutrition, 2024)
Background The relationship between dietary factors and hernias is currently unclear. Methods The UK Biobank was used to extract dietary factors that were used as exposures, including intake of alcohol, non-oily fish, beef, fresh fruit, oily fish, salad/raw vegetables, dried fruit, coffee, cereal, salt, tea, water, cooked vegetables, cheese, Lamb/mutton, pork, poultry, processed meat, and bread. The FinnGen biobank was used to obtain GWAS data on hernias as outcomes. The main analysis of this study was performed using the weighted median, MR-Egger, and IVW methods. Cochran’s Q test was utilized to assess heterogeneity. To find potential outliers, the MR-PRESSO method was used. Leave-one-out analysis was employed to assess the IVW method’s robustness. Results Alcoholic consumption per week (OR: 0.614; p = 0.00614) reduced the risk of inguinal hernia. Alcohol intake frequency (OR: 1.309; p = 0.0477) increased the risk of ventral hernia (mainly including incisional hernia and parastomal hernia). The intake of non-oily fish (OR: 2.945; p = 0.0214) increased the risk of inguinal hernia. Salt added to food (OR: 1.841; p = 0.00267) increased the risk of umbilical hernia. Cheese intake (OR: 0.434; p = 0.000536) and dried fruit intake (OR: 0.322; p = 0.00716) decreased the risk of ventral hernia, while cooked vegetable intake (OR: 4.475; p = 0.0380) increased the risk of ventral hernia. No causal relationships were found with hernias from other dietary factors. Conclusion Inguinal, umbilical, and ventral hernias are all related to dietary factors.